Analisis Pertumbuhan Sapi Potong di Kabupaten Pinrang - Syam, Jumriah; Irsyad, Muhammad; Jamili, Muhammad Arsan (Universitas Islam Negeri Alauddin Makassar, 2025)
Gender is a social and cultural construct influencing roles and responsibilities across various sectors, including beef cattle farming under a profit-sharing system. This study aims to analyze gender roles in the management of beef cattle farming within a profit-sharing system in Bontocani District, Bone Regency. The research sample consisted of 36 farmers, 24 men, and 12 women, selected proportionally with a significance level of α=10%. Data collection was conducted using a cross-sectional survey method. Data analysis was performed descriptively to examine gender roles in access, control, and the utilization and management of profits. The findings indicate that men dominate access to resources (65–67%), decision-making control (61–64%), and external profit utilization (78%), while women play a more significant role in internal profit utilization (81%). The study concludes that gender roles influence the management of beef cattle farming, with men being more dominant in strategic and economic aspects. In contrast, women are more involved in profit management within the domestic sphere. Collaboration between men and women is a key factor in ensuring the sustainability of this farming business.